The Italian coronavirus disease 2019 outbreak: recommendations from clinical practice. (30th March 2020) - Sorbello, M.; El‐Boghdadly, K.; Di Giacinto, I.; Cataldo, R.; Esposito, C.; Falcetta, S.; Merli, G.; Cortese, G.; Corso, R. M.; Bressan, F.; Pintaudi, S.; Greif, R.; et al.
Summary: Novel coronavirus 2019 is a single‐stranded, ribonucleic acid virus that has led to an international pandemic of coronavirus disease 2019. Clinical data from the Chinese outbreak have been reported, but experiences and recommendations from clinical practice during the Italian outbreak have not. We report the impact of the coronavirus disease 2019 outbreak on regional and national healthcare infrastructure. We also report on recommendations based on clinical experiences of managing patients throughout Italy. In particular, we describe key elements of clinical management, including: safe oxygen therapy; airway management; personal protective equipment; and non‐technical aspects of caring for patients diagnosed with coronavirus disease 2019. Only through planning, training and team working will clinicians and healthcare systems be best placed to deal with the many complex implications of this new pandemic.